2023
DOI: 10.5152/tjg.2022.211010
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Kidney Function and Intestinal Biological Characteristics of Adenine and Folium SennaeInduced Diarrhea Model in Mice

Abstract: Background: This study investigated the correlation among kidney function, intestinal enzyme activities, and microbial activity of adenine and Folium sennae -induced diarrhea model in mice, which provided a basis for clinical treatment of kidney-intestinal correlation. Methods: We performed different doses of adenine combined with Folium sennae intragastric administration to establish the animal model of diarrhea. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…In our animal experiment, spleen deficiency constipation could cause weight loss, while the weight increased significantly after SMD intervention, indicating that SMD could help weight recovery, this is probably because SMD has the function of invigorating spleen and stomach, increasing the appetite, and improving its digestion and absorption functions ( Liu, 2014 ). The thymus and spleen are important for establishing the body’s immune function ( Li et al, 2022c ). Therefore, after the intervention of SMD, we examined the spleen and thymus indices.…”
Section: Discussionmentioning
confidence: 99%
“…In our animal experiment, spleen deficiency constipation could cause weight loss, while the weight increased significantly after SMD intervention, indicating that SMD could help weight recovery, this is probably because SMD has the function of invigorating spleen and stomach, increasing the appetite, and improving its digestion and absorption functions ( Liu, 2014 ). The thymus and spleen are important for establishing the body’s immune function ( Li et al, 2022c ). Therefore, after the intervention of SMD, we examined the spleen and thymus indices.…”
Section: Discussionmentioning
confidence: 99%
“…Preparation of FDA stock solution and FDA reaction solution: 2 mg of FDA is mixed with 1 mL of acetone to produce 2 mg/mL of FDA stock solution, reserved at 2-8°C and protected from light, added FDA stock solution to sterilized PBS (pH = 7.6) so that the final concentration of FDA reaction solution is 10 μg/mL ( Guo et al, 2022 ; Li X. et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Experimental group: Added 2 mL FDA reaction solution and 50 μL sample into a dry sterilized tube, and the mixture was incubated at 24°C for 90 min, subsequently removed, and added 2 mL acetone was to terminate the reaction. Finally, all samples were determined three times in parallel by UV spectrophotometer at 490 nm, and the microbial activity per unit mass of the sample is expressed as A 490 value ( Guo et al, 2022 ; Li X. et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Our research group’s preliminary research presented that mice showed obvious diarrhea symptoms and caused gut microbiota disorders after the Folium sennae modeling [ 20 ]. Furthermore, we compared the effects of adenine combined with Folium sennae at different doses and days, on the kidney and gut functions in mice and presented that adenine (50 mg/(kg·d), gavaged for 14 days), combined with Folium sennae (10 g/(kg·d), gavaged for 7 days,) significantly caused impairment of the kidney and gut function in mice [ 21 ]. Subsequently, we have successfully constructed and validated a mouse model of diarrhea using the same modeling method as described above, thus confirming the reliability of the model [ 22 ].…”
Section: Introductionmentioning
confidence: 99%